2008
DOI: 10.1080/10426910802385059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed Rate on Tool Wear in Milling of Al-4%Cu/B4CpComposite

Abstract: The effect of feed rate on tool wear in milling of B 4 C p reinforced aluminum metal matrix composites (MMCs), produced by liquid phase sintering method, was investigated. Milling experiments on these composites were conducted with three different types of cementide carbide tools (uncoated, double coated (TiN + TiAlN) and triple coated (TiCN + Al 2 O 3 + TiN)) for three different feed rates of 0.15 mm/z, 0.20 mm/z, and 0.25 mm/z. After milling experiments, an optical microscope was used to measure the magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In milling the composite, experimental results showed that flank wear of all of the investigated tools decreased as the feed rate increased at the same chip volume. 42 Tool wear showed an inverse relation to feed rate at the same cutting depth during the drilling process of metal-matrix composites. 43 Since exponent a /2 is small (approximately 0.3), the edge radius indicates no significant difference within the experimental range.…”
Section: Resultsmentioning
confidence: 97%
“…In milling the composite, experimental results showed that flank wear of all of the investigated tools decreased as the feed rate increased at the same chip volume. 42 Tool wear showed an inverse relation to feed rate at the same cutting depth during the drilling process of metal-matrix composites. 43 Since exponent a /2 is small (approximately 0.3), the edge radius indicates no significant difference within the experimental range.…”
Section: Resultsmentioning
confidence: 97%
“…For example, diamond blades cannot be used effectively when milling a composite reinforced with a 65% volumetric fraction of 10 μm SiC particles at a speed of above 300 m/min [26]. An interesting phenomenon was observed when machining an aluminium composite reinforced with short fibres and particles by means of tools made of respectively uncoated carbide and coated carbide [24]. Below the cutting speed of 250 m/min, cracks and spalls appeared, while above this speed the abrasive wear of the tool flank increased considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that at higher feed rates, the rate of abrasive wear on the cutting tool decreases [93][94][95][96]. One of these studies attributes the decrease in wear to the thermal softening of the workpiece material as interface temperature rises [19].…”
Section: Effect Of Feed Ratementioning
confidence: 99%